Perceived Barriers to Implementing Sustainable Construction Practices among Small and Medium-Sized Enterprises (SMEs) in Nigeria - Idris, Abdullahi; Okeniyi, Abdullateef Bayo; Ajibade, Yusuff Adelabu; Ujong, Jesam Abam; Abdulraheem, Aliyyu Abiola (Journal of Sustainability and Environmental Management, 2024)
Adopting sustainable construction practices is critical for mitigating the environmental impact of the construction industry, yet Small and Medium-Sized Enterprises (SMEs) in Nigeria face significant challenges in embracing these practices. Despite the industry's substantial contribution to the country's economy, the integration of sustainability within SMEs remains limited, raising concerns about the sector's long-term environmental sustainability. This study aims to identify and analyse the perceived barriers to sustainable construction practices among SMEs in Abuja, Nigeria. Using a quantitative research design, data were collected through structured questionnaires from 116 SME owners, managers, and key decision-makers. The analysis revealed that financial constraints, lack of expertise, regulatory challenges, and technological complexity are the most significant barriers hindering the adoption of sustainable practices. The study also found no statistically significant differences in the perception of these barriers between small and medium enterprises, suggesting that these challenges are widespread across different enterprise sizes. The findings highlight the need for comprehensive policy interventions, financial support, and targeted training programs to help SMEs overcome these barriers. This study provides valuable insights for policymakers and industry stakeholders and contributes to the broader discourse on promoting sustainability in the construction industry.